Digital Storytelling as a Meaningful Learning Strategy in Online Learning - Saptiwi Rohayati; Nur Arifah Drajati; Joko Nurkamto (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to ascertain students' perceptions of the use of digital storytelling as a meaningful learning strategy in an online environment at a senior high school in Indonesia. The case study method was used in this study, which included twenty-eleventh-grade students as participants. The data analyzed in this study come from a student questionnaire, a semi-structured interview, and five-week classroom observation. This qualitative study indicated that students viewed digital storytelling as an instructional method capable of involving them in an active, authentic, and purposeful learning environment. Additionally, digital storytelling enhances students' exposure to a variety of skills and collaborative work portfolios. The study's practical implications for teachers implementing digital storytelling are to allow additional time for content acquisition and comprehensive learning reflection.